PHONOLOGICAL OBJECTIVES OF THREE YEAR OLD CHILDREN - Basuki Rachmat Sinaga (BAHASTRA, 2018)
This research aimed to describe language acquisition in the phonology. The method of the research was a qualitative descriptive by observation and technique of noting. The data source of the research was a record of voice of a three year four month year old child named Wesly when singing two songs of children movie shows of "Tayo" and "Rainbow Ruby." The result of the research showed that the child has been able to speak the understandable language. On the other hand, there were still some difficulties in pronouncing the correct and good phoneme. They could be seen in the difficulty of 1) phoneme pronunciation on consonant-type plosive sound; 2) phoneme pronunciation on vowel sound. There were seven forms of plosive sound for the difficulty of phoneme pronunciation of the consonant plosive sound, such as: 1) bilabial, 2) lamino-palatal, 3) apico-alveolar, 4) , 5) dorso velar, 6) alveolar, and 7) lamino-patal. In addition, there was one form of sound for the difficulty of phoneme pronunciation of the vowel sound namely the diphthong phoneme.Keywords: Language, Language Acquisition, Phonology.Â